Effect of Nutritional Status and Associated Factors on Pneumonia Treatment Outcome among Under-Five Children at St. Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia - Hailemariam, Bizuhareg Teka; Legesse, Tesfaye Girma; Alemu, Kassahun (International Journal of Child Health and Nutrition, 2018)
Acute respiratory infection is still a major health problem among under-five children specifically in Ethiopia, where 38% of them are reported as living in the status of under-nutrition. However, there are studies limitation regarding the relationship of nutritional status of under-five children and outcome of pneumonia treatment. Institutional based cross-sectional study design had been employed to see the Effect of nutritional status and associated factors on pneumonia treatment outcome among under-five children in 2015. Data was collected using interview administered structured questionnaires and anthropometric measurement. The study revealed that high probability of poor pneumonia treatment outcome 26(40%) among exposed groups. Those children to house wife mothers 11(16.92%), smoker family member 6(9.23%), non-fully immunized 9(13.85%), less than 500birr spent for a child 26(40%) are observed to be with poor pneumonia treatment outcome. The risk of poor pneumonia treatment outcome was 4 times and 5 times more like among children who lives with smoker family member and exposed groups respectively. But it was 0.075 and 0.05 times less like among Children from urban and whom their monthly budget is 1000 birr or more respectively. Child nutritional status has significant effect on pneumonia treatment outcome among under-five children. Undernourishment, smoker family member, rural residency, monthly budget are among factors impact pneumonia treatment outcome. Nutritional education, Mother education, Employing mothers, Budgeting more than 500 birr per child per month, alleviate smoking among the family member, Limiting family members number per house hold, All children should feed colostrums and Full immunization should be done